MULTIDRUG-RESISTANT Salmonella sp. ISOLATED FROM SEVERAL CHICKEN FARMS IN WEST JAVA, INDONESIA - Aprilia Hardiati; Safika Safika; Fachriyan Hasmi Pasaribu; I Wayan Teguh Wibawan (Universitas Syiah Kuala, 2022)
This study was aimed at isolating and identifying Salmonella sp. and then conducting an antibiotics susceptibility test in order to detect resistant genes. One hundred and five chicken cloaca swab samples were used in this study. 30 samples were taken from a layer farm in Bogor, 45 from a broiler farm in Sukabumi and 30 from a broiler farm in Cianjur. In order to isolate and identify the bacteria, a tetrathionate broth was used, which was then cultured in a Salmonella-Shigella agar, and finally a Gram stain and biochemical test was conducted. To confirm the presence of Salmonella sp., a pair of primers were used for the polymerase chain reaction (PCR) method to determine the presence of the invA gene.. An antibiotics susceptibility test was used with the Kirby-Bauer disk diffusion method. Nine antibiotics were used in this study. Each primer pair was used for the detection of tetA, blaTEM, aac(3)-IV, gyrA and ermB genes, and for genes encoding antibiotic resistance a PCR test was used. Eight (7.6%) Salmonella sp. were isolated in this study. All isolates showed positive results with PCR confirmation. The results of the antibiotics susceptibility test showed that Salmonella sp. isolates were resistant to tetracycline (75%), oxytetracycline (75%), amphicillin (75%), gentamycin (12.5%), nalidixic acid (100%), ciprofloxacin (12.5%), enrofloxacin (0%), erythromycin (100%), and chloramphenicol (0%). The distribution of antibiotic resistance genes in Salmonella sp. were tetA (33.3%), blaTEM (100%), aac(3)-IV (0%), gyrA (100%) and ermB (0%) positive. In conclusion, Salmonella sp. was isolated. All isolates showed positive results in the PCR confirmation. Salmonella sp. isolates were resistant to tetracycline, oxytetracycline, amphicillin, gentamycin, nalidixic acid, ciprofloxacin, and erythromycin. Only the tetA, blaTEM, and gyrA genes were detected in Salmonella sp. isolates.